2008
DOI: 10.1016/j.pscychresns.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum volume and eyeblink conditioning in schizophrenia

Abstract: Although accumulating evidence suggests that cerebellar abnormalities may be linked to the symptoms and course of schizophrenia, few studies have related structural and functional indices of cerebellar integrity. The present study examined the relationship between the volume of specific subregions of the cerebellum and cerebellar function, as measured by eyeblink conditioning. Nine individuals with schizophrenia and six healthy comparison participants completed structural magnetic resonance imaging of the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 68 publications
2
39
0
Order By: Relevance
“…Findings from these animal studies are supported by the human literature (Perrett et al, 1993; Garcia et al, 1999). Moreover, in healthy volunteers, increased anterior lobe volume is associated with later CR peak responses that occur closer to UR onset (Edwards et al, 2008). Later CRs can be considered more adaptive than earlier ones because it is more likely to avoid the aversive unconditioned stimulus, in this case an airpuff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from these animal studies are supported by the human literature (Perrett et al, 1993; Garcia et al, 1999). Moreover, in healthy volunteers, increased anterior lobe volume is associated with later CR peak responses that occur closer to UR onset (Edwards et al, 2008). Later CRs can be considered more adaptive than earlier ones because it is more likely to avoid the aversive unconditioned stimulus, in this case an airpuff.…”
Section: Discussionmentioning
confidence: 99%
“…Most auditory delay EBC studies have found impaired conditioning in schizophrenia (Hofer et al, 2001; Brown et al, 2005; Edwards et al, 2008; Bolbecker et al, 2009b), although one study reported no differences in conditioning (Marenco et al, 2003), and another found facilitated learning (Sears et al, 2000). Earlier CR peak and onset latencies have also been rather consistently reported (Sears et al, 2000; Brown et al, 2005; Bolbecker et al, 2009b); however, Marenco et al (2003) reported later CR peak and onset latencies.…”
Section: Introductionmentioning
confidence: 99%
“…Early work examining eyeblink conditioning in schizophrenia using behavioral measures has suggested that patients condition faster than controls and have a higher percentage of CRs (Spain, 1966; Sears et al, 2000). However, more recent studies have reported the opposite result (Hofer et al, 2001; Brown et al, 2005; Edwards et al, 2008; Bolbecker et al, 2009, 2011) indicating eyeblink conditioning deficits in schizophrenia.…”
Section: Introductionmentioning
confidence: 89%
“…EBC does not depend upon verbal or social interaction and simple modifications of the paradigm can probe the functioning of different levels of the brain. Furthermore, EBC performance has been shown to be sensitive to functional impairments in an array of disorders including attention deficit hyperactivity disorder (Frings et al, 2010), fetal alcohol syndrome (Coffin et al, 2005; Jacobson et al, 2008, 2011), schizophrenia (Sears et al, 2000; Edwards et al, 2008), Fragile-X (Koekkoek et al, 2005), depression (Greer et al, 2005), post-traumatic stress disorder (Burriss et al, 2007), dyslexia (Coffin et al, 2005; Nicolson et al, 2002), and neurodegenerative diseases such as Huntington’s (Woodruff-Pak and Papka, 1996), and Alzheimer’s (Woodruff-Pak, 2001). There are two general forms of EBC: trace and delay.…”
Section: Introductionmentioning
confidence: 99%